TRANSCRIPTOME ANALYSIS OF FLOWER BUDS AT THREE DIFFERENT DEVELOPMENTAL STAGES IN Cymbidium kanran - Weiyi Li; Shaofan Li; Wu Xinchen; Yang Boyun; Huolin Luo (Journal of Animal and Plant Sciences, 2024)
Cymbidium kanran is extensively cultivated and globally coveted, enjoying widespread popularity in horticulture circles. Despite its popularity, the intricate mechanisms underlying its flowering cycle have remained largely enigmatic. In this study, we conducted transcriptome sequencing on flower buds at three distinct stages, including the initiation of flower bud differentiation, the differentiation stage of flower primordium, and the stage of flower bud formation. This investigation aimed to unravel the flowering mechanism of the target species. Differential gene expression was screened and subjected to pathway enrichment analysis to identify key pathways involved in flowering regulation. Subsequently, the identified differentially expressed genes within these critical pathways were validated using RT-qPCR. The results showed that a total of 23720 differentially expressed genes (DEGs) were obtained. Through Gene Ontology (GO) functional annotation, it was found that it involved three categories of cellular component, biological process and molecular function, including 46 subcategories. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis found that it was mainly enriched in metabolic pathways and biosynthetic of secondary metabolites pathways. In addition, this study found 29 genes related to four flowering regulatory pathways and flowering integration, including a gene related to autonomic pathway, five genes related to vernalization pathway, 13 genes related photoperiod pathway, four genes related to gibberellin (GA) pathway, and six genes related to flowering integration. Through RT-qPCR analyses, it was found that the relative expression of genes in RNA-seq was accurate and reliable. This study preliminarily revealed the molecular mechanism of flowering inC. kanran, and the results laid a foundation for the molecular regulation mechanism of flowering in C. kanran, and also provided a basis for the regulation of flowering period of orchids.
Keywords: Cymbidium kanran; transcriptome; flowering regulation; differentially expressed gene